Mechanism of Enhancing the Inhibitory Effect of Metschnikowia rubicola on Apple Penicilliosis by Cofactors - Jingting DU; Nan LIN; Longmei CONG; Junyue HU; Junfeng SHI; Yuqing GE; Qian ZHANG (Shipin gongye ke-ji)
The Metschnikowia rubicola obtained from laboratory screening could effectively inhibit the occurrence of postharvest apple penicillium rot. In order to improve the inhibitory effect of M. rubicola on apple penicillium rot, cofactors with M. rubicola were screened. The mechanism of cofactors in enhancing the resistance of M. rubicola to penicilliosis was explored by compared the activity of M. rubicola, the spore germination and hyphal growth of Penicillium expansum, the activity of resistance related enzymes, and the degradation of PAT before and after adding cofactors. The results showed that the addition of 5 g/L AOS or 4 μmol/L PA could effectively improve the control effect of M. rubicola on apple penicilliosis and reduce the spore germination and mycelial growth rate of P. expansum. The addition of AOS was more significant, resulting in inhibition rate increases of 21.67% and 31.40%, respectively. AOS or PA could also enhance M. rubicola's colonization ability on apple wounds and surfaces. Increased the activity of enzymes related to the phenylpropane metabolic pathway (PPO, POD, PAL, CAD, C4H, 4CL, CHI, GLU) and the content of lignin, total phenols, and flavonoids significantly on apples. M. rubicola induced by AOS could enhance its ability to degrade PAT. Overall, the addition of AOS or PA could effectively enhance the preventive and therapeutic effects of M. rubicola on apple penicillium disease, and AOS could also enhance M Rubicola's ability to degrade PAT.